The Role of Interest and Enjoyment in Determining Students’ Approach to Learning - Andrew G Holmes (Educational Process: International Journal)
This paper provides information about findings from a recent research project that provides a new insight into how students’ approaches to learning may be impacted by their level of interest in and enjoyment of the topic being studied. The data from this research suggests that for contemporary students, interest and enjoyment play an important role in determining their approach to learning. As such there are implications for all educators who may wish to encourage their students to use a deep approach to learning.